Bacterioplankton production in freshwater Antarctic lakes - Laybourn-Parry, J; Henshaw, T; Jones, DJ; Quayle, W (2004)
1. Bacterioplankton production was measured in the water columns of two ultraoligotrophic, freshwater Antarctic lakes (Crooked Lake and Lake Druzhby) during an annual cycle. In both lakes bacterial production, measured by the incorporation of [3H] thymidine, continued in winter and showed a cycle over the year. The range of production was between 0 and 479 ng C L)1 h)1 in Crooked Lake and 0–354 ng L)1 h)1 in Lake Druzhby. 2. Abundance and mean cell volume both varied, producing marked changes in biomass during the year, with highest biomass occurring in the winter and early spring. Biomass showed similar seasonal trends in both lakes. 3. For most of the year inorganic forms of nitrogen and phosphorus were detectable in the water columns of the lakes and were unlikely to have limited bacterial production. Dissolved organic carbon (DOC) was below 3000 lg L)1. Dissolved amino acids and carbohydrates contributed 5–25% of the DOC pool in Crooked Lake and 5–64% in Lake Druzhby. Dissolved carbohydrates were consistently low, suggesting that this may have been the preferred carbon substrate for bacterioplankton. 4. Aggregate associated bacteria had higher mean cell volume, abundances and production than freely suspended bacteria in Lake Druzhby, while in Crooked Lake aggregate associated bacteria consistently had higher mean cell volumes than free bacteria, but abundance and production were on occasion higher in free bacteria compared with aggregate associated communities. 5. The data indicated that production is limited by continuous low temperatures and the limited availability of suitable DOC substrate. However, the bacterioplankton functions year round, responding to factors other than temperature.